Penggunaan Analisis Biplot dalam Pengelompokan Kabupaten/Kota di Provinsi Sulawesi Selatan Berdasarkan Indikator Kesejahteraan Masyarakat - Rangkuti, Yulita Molliq; Landong, Ahmad; Tarigan, Dewan Dinata (Journal of Mathematics, Computations and Statistics, 2023)
Fixed free beam is one of the components that are most often used as raw materials for furnitureand building construction. The use of wooden beams is inseparable from several important issues that mustbe taken into account, including stiffness, strength, stability, and flexibility. The problem of free vibrationthat occurs in wooden beams must also be taken into account. All systems that have mass and elasticity canexperience free vibrations or vibrations that occur without external stimulation. This free vibration occurswhen the system on the object oscillates due to the work of the forces that exist in the system itself (inherent).The free vibration of the wooden beams must be overcome by damping, so that it does not seriously affectthe structure of the strength, stability, and flexibility of the wooden beams. Damping can be done by lookingfor free vibration points or vibration mode shapes on fixed free beams. One approach that can be used tofind the mode shapes is a numerical approach using the Reyleigh-Ritz method. The methodology used isthe development of a python script to find free vibration modes on the beam. In this article, the beam with a length of 0.5 meters and a thickness of 2.25 × 10^−4 meters is selected as a simulation model.